Analisis Kinerja Keuangan pada Pemerintahan Kabupaten Nagekeo - Wela, Hipolitus Tua; Tanusi, Gabriel; Langga, Lambertus (SCIENTIFIC JOURNAL OF MANAGEMENT AND BUSINESS (SJMB), 2021)
The purpose of this study was to determine the financial performance of Nagekeo Regency seen fro the decentralization degree ratio, regional financial dependency ratio, regional financial dependency ratio, regional financial independence ratio, PAD effectiviness ratio, and regional financial efficiency ratio. This type of research is descriptive qualitative and quantitative research. Qualitative data, namely data presented in the form of verbal words instead of numbers, which means qualitative data in this study is a general description of the object of research, including a brief history of its establishment, geographical location, objects, vision and mission, and organizational structure. and quantitative data, types of data that can be measured directly in the form of information or explanations expressed in numbers or numbers. In this case the quantitative data required is the 2014-2018 Regional Budget Realization Report. The results of this study indicate that (1) the ratio of the degree of decentralization can be categorized as Very Less, because it is still in the interval scale of 00.00% -10.00%. Consecutively from 2014 to 2018 the ratios were: 4.62%; 4.55%; 4.11%; 6.08%; and 4.43%. (2) The Ratio of Regional Financial Independence is still very low and the pattern of the relationship is Instructive, because it is still included in the 0% -25% interval. Consecutively from 2014 to 2018 the ratios were: 4.85%; 4.77%; 4.34%; 6.48%; and 4.75%. (3) The effectiveness ratio of PAD is known that the financial effectiveness of the DPPKAD Nagekeo Regency in 2016 is effective because its effectiveness is still below 100%, which is 95.67%. 2014, 2015, 2017, and 2018 were very effective because the value obtained was more than 100%, namely 102.81%; 107.83%; 100.01%; and 105.37%. (4)